A study of oil and gas producers subsector portfolio using the trade-off ranking method - Muhammad Akram Ramadhan, Ibrahim; Nor Izzati, Jaini; Hafizah, Bahaludin (2024)
In the topic of stock selection, numerous multi-criteria decision-making (MCDM) techniques have been applied to handle selection difficulties. This paper proposes a compromise approach for the subsector stocks of oil and gas companies, motivated by the pandemic crisis and the political issue in Malaysia. The paper presents a novel analysis of the existing trade-off ranking (TOR) method for ranking the stocks of oil and gas producers in conflicting multi-criteria problems. As a result, the TOR technique ranks the subsector stocks effectively for two criteria weights. Comparison with TOPSIS shows that both methods exhibit similar performance.